(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the microbiological characteristics and evaluate the treatment outcomes of ventilator-associated pneumonia (VAP) caused by Acinetobacter baumannii at the Center for Anesthesia and Resuscitation – Bach Mai Hospital. Subjects: A cross-sectional descriptive study was conducted on 51 patients diagnosed with VAP due to A. baumannii, admitted to the Surgical Intensive Care Unit – Center for Anesthesia and Resuscitation, Bach Mai Hospital, from January 2025 to October 2025. Results: Antibiogram results indicated extremely high resistance rates of A. baumannii to most conventional antibiotic groups. Specifically, the resistance rate was 98% for both the Carbapenem group (Imipenem, Meropenem) and the Cephalosporin group (Ceftazidim, Cefepim). Resistance to Quinolones and Aminoglycosides ranged from 92.2% to 96.1%. However, 100% of the isolates remained susceptible to Colistin. Minocycline showed a sensitivity rate of 41.2% and an intermediate rate of 51%. Regarding the resistance mechanism, 98% of the strains produced Betalactamase Group D enzyme. In terms of treatment, 96.1% of patients received combination therapy , with the most common regimen being high-dose Colistin + Ampicillin/Sulbactam + Meropenem (37.2%). The treatment outcomes demonstrated a survival rate of 80.4% and a mortality rate of 19.6%. Conclusion: A. baumannii causing VAP in the studied unit exhibited a high level of multidrug resistance, primarily associated with the production of Betalactamase Group D. Colistin is currently the only antibiotic maintaining absolute susceptibility. The strategy of combination antibiotic therapy centered on Colistin has yielded positive clinical outcomes.